AnkleGlide: A continuous ankle flexion device for Long-Term Bedridden patients - Raiyun Kabir; Mrinmoy Nandi Bappa; Raisa Islam; Tarikul Hamid; Shams Nafisa Ali; Jahid Ferdous (Journal of Orthopaedic Reports)
Background: Prolonged immobility in response to some medical conditions like major surgery, stroke, and neuromuscular diseases may lead to significant effects in the form of deep vein thrombosis (DVT) and muscle atrophy. Maintaining adequate and consistent blood supply to the blood vessels is essential for preventing DVT and muscle atrophy. Sequential Compression Devices (SCDs), used to mitigate blood clot risks and featuring inflatable and deflatable cuffs, gently contract leg muscles. However, it costs about 50 USD daily, a sum too steep for many in low- and middle-income countries. Therefore, we aimed to develop a simple, affordable, and functional alternative to reduce DVT and muscle atrophy risks and facilitate early rehabilitation. Methods: The AnkleGlide is designed using SolidWorks with two servo motors inspired by satellite pan expansion mechanisms, enabling plantarflexion and dorsiflexion. The device operates on an Arduino NANO and a mobile app that controls speed and cycle count via a Bluetooth module. The developed prototype matches the computer-aided design specifications and ensures a range of ankle joint motion to improve circulation by promoting calf muscle activity at an affordable cost. Results: The AnkleGlide significantly improved lower limb blood circulation, characterized by increased peak systolic velocity and flow rate in the popliteal artery after 50, 100, and 200 cycles of AnkleGlide operation. Statistical analysis confirmed that 100 and 200 cycles produced significant improvements. The study demonstrated a clear upward trend in circulation enhancement. Conclusion: The study shows that AnkleGlide is effective in improving lower limb blood circulation to alleviate the risks of DVT and muscle atrophy in immobilized patients. Its convenient design and control make it a practical solution for ICU and rehabilitation settings. Further developments may include enhanced movement capabilities and early DVT sensing features.